2018
DOI: 10.1158/1535-7163.mct-17-0604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tissue and Circulating Tumor DNA by Next-Generation Sequencing of Hepatocellular Carcinoma: Implications for Targeted Therapeutics

Abstract: Hepatocellular carcinoma (HCC) has limited treatment options. Molecular analysis of its mutational landscape may enable the identification of novel therapies. However, biopsy is not routinely performed in HCC. The utility of analyzing cell-free circulating tumor DNA (ctDNA) by next-generation sequencing (NGS) is not established. We performed 32 ctDNA NGS analyses on 26 patients; 10 of these patients had tissue NGS (236 to 626 genes). ctDNA was evaluated using an assay that detects single nucleotide variants, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 45 publications
5
42
0
Order By: Relevance
“…[74][75][76] The mutational profile of cfDNA was further shown to reflect the status in the corresponding tumour tissues. 77 Currently, mutational analysis in patients with HCC is not routinely used to guide treatment decisions for 2 reasons. First, there are only 6 approved systemic therapies for HCC, including sorafenib and lenvatinib as first-line treatments for advanced HCC and regorafenib, cabozantinib, nivolumab and pembrolizumab as second-line treatments for patients who were previously treated with sorafenib or lenvatinib.…”
Section: Cnamentioning
confidence: 99%
“…[74][75][76] The mutational profile of cfDNA was further shown to reflect the status in the corresponding tumour tissues. 77 Currently, mutational analysis in patients with HCC is not routinely used to guide treatment decisions for 2 reasons. First, there are only 6 approved systemic therapies for HCC, including sorafenib and lenvatinib as first-line treatments for advanced HCC and regorafenib, cabozantinib, nivolumab and pembrolizumab as second-line treatments for patients who were previously treated with sorafenib or lenvatinib.…”
Section: Cnamentioning
confidence: 99%
“…Confirming tumor heterogeneity in HCC, a recent study analysed plasma cfDNA from 26 HCC patients for the presence of mutations in a large set of genes. Authors found tumor heterogeneity and evolution over time by tracking circulating mutation pattern in a patient who developed progression after capecitabine treatment [29] .…”
Section: Cancer Gene Mutations In Plasma or Serum Cfdnamentioning
confidence: 99%
“…Another study in advanced liver cancer demonstrated that serial assessment of alterations in cancer-related driver genes using cfDNA NGS can reveal genomic changes with time. The concordance levels between genomic alterations found in plasma and tissue were high for the three most commonly altered genes, TP53, CTNNB1, and ARID1A, indicating that liquid biopsy is relatively accurate compared to traditional biopsy in monitoring of advanced liver cancer patients [32]. Cai et al demonstrated that both single nucleotide variants (SNVs) and copy number variants (CNVs) of cfDNA found in plasma samples can quantifiably reflect the tumor size of liver cancer patients and may be prognostic [33].…”
Section: Liver Cancermentioning
confidence: 99%